Black Cat, White Cat: The Identity of the WTO Judges - Louise Johannesson; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2015)
WTO judges are proposed by the WTO Secretariat and elected to act as judges' if either approved by the parties to a dispute, or by the WTO Director-General in case no agreement between the parties has been possible. They are typically Geneva crowd', that is, they are either current or former delegates representing their country before the WTO. This observation holds for both first- as well as second instance WTO judges (e.g. Panelists and members of the Appellate Body). In that, the WTO evidences an attitude strikingly similar to the GATT. Whereas the legal regime has been heavily legalized', the people called to enforce it remain the same.
Keywords: K40; 330; Dispute resolution; Panelists; Judicial appointments